Narrative Roles Among Contact Versus Noncontact Sexual Offenders. (October 2019) - Hamilton, Emma; Sanchez, Delida
The current study explored narrative roles among individuals convicted of a sexual offense. Narrative roles in a criminal context are defined as specific personal accounts utilized by offenders to justify illegal behavior. The chosen theoretical framework recognized four primary offender roles: Revengeful Mission/Romantic Quest, Professional, Victim, and Tragic Hero. A total of 23 interviews were conducted with individuals convicted of a sexual offense ( n = 11 contact, n = 12 noncontact) to explore and compare narrative roles between contact and noncontact offenders. Interviews were conducted using a phenomenological approach and coded via Framework Analysis, a qualitative data analytic method. Findings revealed a general pattern of narrative themes among offenders, along with a tendency for contact offenders to endorse Revengeful Mission/Romantic Quest narrative roles and noncontact offenders to endorse Tragic Hero narrative roles. Findings suggest that incorporating narrative roles into conceptualization and treatment of sexual offenders may help with tailoring treatments more effectively.